Innate predisposition to immune escape in follicular lymphoma cells - Gravelle, Pauline (Landes Bioscience, 2012)
Tumor-intrinsic immuno-resistance is a prerequisite for emergence of follicular lymphomas. Here we show that in vitro, such cells are more resistant to immune cytolysis when grown as follicle-mimicking tridimensional aggregates than when grown as cell suspensions. So in patients, this innate adaptation to tumor immunity might precede its selective pressure.